EVALUASI KINERJA BATERAI PACK LiFePO4 DALAM MENYEDIAKAN ENERGI UNTUK POMPA AIR SHIMIZU PS-135 E - Arnold J. Kastanja; Luwis H. Laisina; Nikodemus Lewier (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Lithium iron phosphate (LiFePO4) dikenal karena stabilitas termal dan siklus hidup yang panjang, Lithium iron phosphate( LiFePO4) is known for its thermal stability and long cycle life, making it ideal for energy storage applications and electric vehicles. This research aims to design and implement a LiFePO4 battery pack for the Shimizu PS-135 E water pump system, replacing conventional energy sources. The research methodology includes a literature review, experimental design, prototyping, and performance testing. The battery pack design uses a 4S- 7P configuration with a capacity of 39.35 Ah and a Daly 4S 60A BMS. The results indicate a charging time of 9.4 hours and a discharging time of 1.3 hours, with a produced water volume of 2,182 liters. This study confirms that the LiFePO4 battery pack can meet the pumps power requirements with high efficiency and provides environmental benefits by reducing greenhouse gas emissions and dependence on fossil fuels.